Hemodiálise: controle de infeção, qualidade microbiológica do líquido de diálise versus reuso de dialisadores - Sturmer, Fabiana de Cássia Romanha (2023)
Introduction: The high incidence of complications originating from venous accesses has stimulated the development of research based on the environment were hemodialysis sessions. In this context, the microbiological quality of the dialysis liquid is directly related to the occurrence of compatibility and pyrogenic reactions in patients. Objectives: To investigate the quality of the dialysis liquid and its relationship with the reuse of dialyzers in a hemodialysis clinic. Material and methods: This thesis is divided into an article and a manuscript. The article 1 investigate the presence of microorganisms in the dialysis liquid by centrifugation method, identification, detection of virulence factors, as well as the production of biofilm, in addition to the analysis of the antimicrobial susceptibility profile. The manuscript 1 comparatively analyzed of single-use and reuse hemodialysis dialyzers. The results of article 1 showed the presence of elements from the Bacillus cereus even when following ultra-pure standards, detected by a centrifugation method, with toxin production, and biofilm production with greater evidence at 25 oC and high resistance profile. As for the results of manuscript 1, based on analyzes of single-use and reusable dialyzers, the microbiological analyzes referring to mesophiles, coliforms, and Pseudomonas aeruginosa resulted negative, regarding the presence of microorganisms, in all stages analyzed for assessment of the single-use and reuse dialyzer’s internal liquid (20x). The analysis of samples of cannula fragments resulted negative for bacterial growth in 24/48h when incubated at 37 oC. The fibers of the single-use and reusable capillaries were preserved after 20 uses compared to the single-use capillaries, as evidenced by SEM. Through chemical analyzes, residues that match blood products and proteins were not evidenced. As conclusions, the impact and scientific contribution of this work are based on the discovery of a new technique, by centrifugation for the detection of microorganisms, even by following ultra-pure standards, associated with the production of biofilms. Thus, the detection of synergistic combinations can be a useful and promising tool for reducing the antimicrobial application dose, contributing to mitigating the increase of resistant strains. The results shown in the study demonstrated that, from the microbiological point of view, the reuse of the dialyzer was safe compared to the single-use type, being, thus, considered adequate. Reusing dialyzers for hemodialysis can help reduce the cost of hemodialysis.